The development of a European questionnaire for quality of life in patients with vertebral osteoporosis. - Lips, P; Agnusdei, D; Caulin, F; Cooper, C; Johnell, O; Kanis, J; Liberman, U; Minne, H; Reeve, J; Reginster, J; Vernejoul, d; Wiklund, I (1996)
The complaints of vertebral osteoporosis usually result from wedge or crush fractures and biconcave deformities. These are caused by a decrease of bone mass and deterioration of bone structure leading to loss of strength. Treatment of osteoporosis should result in an increase of bone mass, and the incidence of new vertebral fractures should diminish. However, new vertebral fractures are not always accompanied by pain, and disability does not well correlate with the number of vertebral fractures. Patients with osteoporosis often have other problems e.g. with taking a shower, preparing meals, gardening, walking stairs, visiting friends and attending social activities. In addition, pain and disability may influence mood and lead to depression. The assessment of quality of life should be a primary endpoint in clinical trials in patients with osteoporosis and in individual patients care. Recently, the European Foundation for Osteoporosis (EFFO) has decided a develop a questionnaire for patients with vertebral osteoporosis, i.e. patients with vertebral deformities. The questionnaire is meant for use in clinical trials. A questionnaire was made including 48 questions and 6 visual analogue scales. The questions concern the following domains: pain, activities of daily living, jobs around the house, moving, leisure and social activities, general health perception and mood. The questionnaire ("Qualeffo") has now entered the validation phase. The first study in 8 centres concerns the within-subject reproducibility, the internal coherence, and the specificity by comparing osteoporotic patients with a control group not suffering from osteoporosis or backpain.